Benchmarking Health Systems in Middle East and North Africa Countries - Wang, Huihui; Yazbeck, Abdo S. (Taylor and Francis, 2017)
Health systems are not easy to benchmark, in part because the health sector produces more than one outcome. This article offers two ways of benchmarking the health systems of countries in the Middle East and North Africa (MENA) focusing on two different outcomes, health status and financial protection. The first approach is by measuring the gap between predicted health outcomes based on country socioeconomic status and actual health outcomes. The second approach is by simply comparing the levels of out-of-pocket (OOP) spending in MENA countries. The article offers some interesting findings about the large heterogeneity in both health system outcome achievements despite considerable cultural and linguistic similarities in the region. Moreover, three discrete clusters of countries are found on the health status measure. The findings also give specific health system target outcomes for MENA countries to focus their reform efforts.